Analisis Peran Undewriter Dalam Menyeleksi Risiko pada Produk Asuransi Kesehatan: - Frissai Gusminar Mutia; Fauzi Arif Lubis; Wahyu Syarvina (ManBiz: Journal of Management and Business, 2023)
This study aims at the role of the underwriter in selecting the risk of health insurance products, knowing the obstacles encountered by the underwriter in selecting the risk and the solutions applied to overcome these obstacles, and knowing the underwriting process of group health insurance at AJB Bumiputera Medan. The type of research used is descriptive research, with a qualitative approach. The conclusions of this study briefly are: (1) Underwriters have an important role in insurance companies because underwriters determine whether the insurance coverage can be accommodated by the company or not. (2) Obstacles encountered by underwriters in selecting risks are the availability of incomplete participant data, previous experience data of the insured and prospective insured not providing the desired budget and benefits, while the solution is to contact the agent concerned to obtain additional information needed by the underwriter, apply analysis to groups of prospective insurance participants as new participants, and provide standard premium rates and benefits. (3) The underwriting process begins when marketing applies for SPPA until the issuance of the policy. Keywords: Underwriting, Underwriter, Group Health Insurance